2017
DOI: 10.1002/app.46003
|View full text |Cite
|
Sign up to set email alerts
|

Waterborne poly(urethane‐urea) gas permeation membranes for CO2/CH4 separation

Abstract: In this work, dense membranes from aqueous dispersions of poly(urethane‐urea) (PUU) based on poly(propylene glycol) (PPG) and a block copolymer composed of poly(ethylene glycol) (PEG) and poly(propylene glycol) (PPG), EG‐b‐PG, with 7 wt % of the former were obtained. Nonpolluting formulations were synthesized with proportions of PPG and EG‐b‐PG as 1:0, 1:1, 1:3, and 3:1 in terms of equivalent number ratios. The effect of small and gradual increases in PEG segments was evaluated for the permeability of pure CO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…According to Table 2, the values of total solids ranged from 24 ± 1% to 31 ± 4%, deviating more from the theoretical value of 35%, as PEG segments content increased in formulation. An increment in molar mass of the copolymer provoked an increase in the viscosity of the prepolymer and the need of extra water addition in dispersion stage, causing a decrease in total solids values (7,35). pH values remained in the range of 7.5 ± 1.0 for all systems, being within the ideal range for stable dispersions, specified between 7 and 9 (43).…”
Section: Total Solids and Ph Determinationmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Table 2, the values of total solids ranged from 24 ± 1% to 31 ± 4%, deviating more from the theoretical value of 35%, as PEG segments content increased in formulation. An increment in molar mass of the copolymer provoked an increase in the viscosity of the prepolymer and the need of extra water addition in dispersion stage, causing a decrease in total solids values (7,35). pH values remained in the range of 7.5 ± 1.0 for all systems, being within the ideal range for stable dispersions, specified between 7 and 9 (43).…”
Section: Total Solids and Ph Determinationmentioning
confidence: 99%
“…Let A, A * denote a Leonard pair on V. We can determine whether A, A * is self-du By [ i= denote a standard ordering of the eigenvalues of A. Then A, A * is self-d is a standard ordering of the eigenvalues of A * (see [7,Proposition 8.7]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies reported that polyethylene (PU) glycol‐based polyurethanes are good candidates for use in gas separation membranes . The suppressing crystallization of ethereal groups in polyurethanes can be beneficial for the CO 2 selectivity improvements without a significant loss in the permeability …”
Section: Introductionmentioning
confidence: 99%
“…Polysulfone, polycarbonates, polyimide, Pebax, and polyurethane (PU) are commonly used in polymer‐membrane‐based gas separation . PU has been widely used in gas separation because of its good thermal stability and desirable permeation properties.…”
Section: Introductionmentioning
confidence: 99%